Strategi Komunikasi Kepala Desa dalam Meningkatkan Pendidikan Masyarakat di Desa Karang Mukti Kecamatan Karang Bahagia Kabupaten Bekasi - Yulianto; Marhanani Tri Astuti; Samsudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study is based on the low education level of the community in Karang Mukti Village, Karang Bahagia Sub-district. This situation necessitates communication actions by the village head towards the community and the related village government to improve the community's education level. This study aims to analyze and evaluate the communication strategy of the village head in improving community education in Karang Mukti Village , Karang Bahagia Sub-district, Bekasi Regency. This research uses a descriptive qualitative approach. The data collection techniques in this study are interviews and documentation. The sources of data for this study are the village head, the head of planning, community leaders, and community members in Karang Mukti Village, Karang Bahagia Sub-district, totaling 4 people. The data analysis techniques used in this research are data reduction, data presentation, and verification. The results of this study show that the village head communicates with the community and village apparatus, utilizing public communication and group communication to ensure that the foster parent movement education program in the village and schools can reach the community.